Elemental Characterization of Leaf Extracts of Three Different Species of Mulberry: Morus. alba L., Morus. nigra L. and Morus. indica L., Using Inductively Coupled Plasma -Atomic Emission Spectroscopy (ICP-AES) (International Journal of Scientific Research in Science and Technology, 2024)
The present study aimed to compare the elemental composition of leaf extracts from three different plant species of Mulberry, Morus alba L., Morus nigra L., and Morus indica L. The results showed that ten essential elements of biological importance for human metabolism, such as Copper, Chromium, Iron, Manganese, Sodium, Zinc, Calcium, Nickel, Lead, and Cadmium, were present in varying concentrations, well below the World Health Organization, (WHO’s) daily intake limits. Mulberry leaves are an economical and readily available source of essential mineral elements vital for human health, which can be used to fortify functional foods, treat various diseases, and act as nutraceuticals. The information obtained could be used to determine the efficacy and dosage of herbal drugs manufactured from the leaf extracts of the Mulberry plant, making it a new contributor to food supplements and nutraceutical products.